PENGARUH PROFITABILITAS DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN PADA PT JAYA KONSTRUKSI MANGGALA PRATAMA, Tbk YANG TERDAFTAR DI BURSA EFEK INDONESIA - Riska Andriani; Jubi Jubi; Ady Inrawan; Christine Dewi Nainggolan (JURNAL AKUNTANSI FINANCEIAL STIE SULTAN AGUNG, 2019)
The Purpose of this research is to describe profitability, corporate social responsibility and firm value and to know influence of profitability and corporate social responsibility to firm value at PT Jaya Konstruksi Manggala Pratama, Tbk listed in Indonesia Stock Exchange. The research was using qualitative and quantitative desriptive analysis. The data collection was using documentation. The analysis techniques used are multiple linear regression, correlation coeffient, coefficient of determination, F test and t test.The result of the research are 1. The average of profitability (return on assets) tends to increase, the average of corporate social responsibility (NH Approach) tends to increase, and the average of firm value (price to book value) tends to incrase. 2. The results of multiple linier regression is known that profitability has a negative effect, while corporate social responsibility has a positive effect on the firm value. 3. The results of the analysis of the correlation coefficient and correlation of determination can be concluded that the relationship between profitability and corporate social responsibility to firm value is very high and only a few are influenced by other variables not explained in this study. 4. The results of testing hypotheses can be concluded that profitability has a significant negative effect and corporate social responsibility has a significant positive effect on firm value.As for suggestions from this research are important for the company to maintain the stability of return on assets, NH Approach and price to book valueKeywords: Profitability, Corporate Social Responsibility, and Firm Value